1991
DOI: 10.1002/anie.199101481
|View full text |Cite
|
Sign up to set email alerts
|

The Bioinorganic Chemistry of Vanadium

Abstract: Vanadium is a trace element that plays an important, perhaps essential and general role in the regulation of enzymatic phosphorylations. Several forms of life, including the fly agaric toadstool (Amanita muscaria) and certain sea squirts (ascidians), are able to concentrate vanadium. In other organisms vanadium is part of the active site of some enzymes. Well-studied examples are the nitrogen-fixing bacterium Azotobacter and various seaweeds that use vanadate-dependent peroxidases to synthesize halogenated org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
222
0
4

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 489 publications
(227 citation statements)
references
References 259 publications
(7 reference statements)
1
222
0
4
Order By: Relevance
“…[1][2][3][4][5][6][7] In recent years, the interest to the chemistry of oxovanadates has grown considerably. 8 The increasing interest is mainly owing to the role of vanadium in several biological processes such as the regulation of glucose level in the blood of diabetic animals and patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] In recent years, the interest to the chemistry of oxovanadates has grown considerably. 8 The increasing interest is mainly owing to the role of vanadium in several biological processes such as the regulation of glucose level in the blood of diabetic animals and patients.…”
Section: Introductionmentioning
confidence: 99%
“…8 The increasing interest is mainly owing to the role of vanadium in several biological processes such as the regulation of glucose level in the blood of diabetic animals and patients. 3,4,[9][10][11][12][13][14][15][16][17] Moreover, decavanadate and oxovanadates have many biological activities and been successfully used for the comprehension of several biochemical processes. 18 Other interest for vanadium oxides is sourced from their potential uses as secondary cathode materials, both catalysis and electronics.…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous biochemical and physiological functions have been suggested for this element, and despite the amount of the knowledge so far accumulated, vanadium still does not have a clearly defined role in the higher forms of life. [1][2][3][4][5] The best evidence for a biological role of vanadium comes from bacteria (the so-called alternative nitrogenases in which vanadium replaces molybdenum in the FeMocofactor of some Azotobacter species) [4][5][6][7] and from plants (vanadium-dependent haloperoxidases found in some algae, lichens and fungi). 4,5,8,9 On the other hand, experiments with laboratory animals have shown that vanadium deprivation enhances abortion rates, reduces milk levels during lactation and produces thyroidal disorders.…”
Section: Introductionmentioning
confidence: 99%
“…10 Like molybdenum, vanadium occupies an exceptional position among the bioelements because both, anionic and cationic forms can participate in biological processes. 3,5,11,12 In its anionic forms (vanadates(V)), it resembles phosphates, but in its cationic forms -mainly as VO 2+ -it behaves like a typical transition metal ion, which competes with other metal cations in coordination with biogenic ligands or compounds. This duality, together with the facility with which it changes oxidation states and coordination environments, may be responsible for the very peculiar and somewhat unparalleled behavior of this biometal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation